Efeito da interação gramínea -solo- calagem sobre a eficiência de fosfatos naturais - Martins Moreira , Sônia; Gomide Loures , Emílio; Lima Thiébaut, José Tarcísio; Ferreira Novais , Roberto (Revista Ceres, 2025)
Greenhouse experiments were undertaken in which three species of forage grass were grown in three «cerrado»-type soils, with and without lime, and with rock phosphates from three sources, to determine various interactions among these factors.